Low rates of immediate coronary angiography among young adults resuscitated from sudden cardiac arrest. (1st February 2020) - Waldmann, Victor; Karam, Nicole; Rischard, Julien; Bougouin, Wulfran; Sharifzadehgan, Ardalan; Dumas, Florence; Narayanan, Kumar; Sideris, Georgios; Voicu, Sebastian; Gandjbakhch, Estelle; Jost, Daniel; Lamhaut, Lionel; et al.
Abstract: Aim: Coronary artery disease (CAD) has recently been emphasized as a major cause of sudden cardiac arrest (SCA) in young adults. We aim to assess the rate of immediate coronary angiography performance in young patients resuscitated from SCA. Methods: From May 2011 to May 2017, all cases of out-of-hospital SCA aged 18–40 years alive at hospital admission were prospectively included in 48 hospitals of the Great Paris area. Cardiovascular causes of SCA were centrally adjudicated, and management including immediate coronary angiography performance was assessed. Results: Out of 3579 SCA admitted alive, 409 (11.4%) patients were under 40 years of age (32.3 ± 6.2 years, 69.7% males), with 244 patients having a definite cause identified. Among those, CAD accounted for 72 (29.5%) cases, of which 64 (88.9%) were acute coronary syndromes. The rate of immediate coronary angiography was only 41.7% compared to 65.1% among those ≥40-years (P < 0.001). During the study period, while the rate of immediate coronary angiography increased from 60.5% to 70.3% (P < 0.001) in patients aged ≥40 years, the rate in patients aged less than 40 years remained stable (43.5% to 45.3%, P = 0.795). Patients younger than 40 years were significantly less likely to undergo immediate coronary angiography (OR = 0.34, 95% CI: 0.25–0.47), although early angiography was associated with survival at hospital discharge (OR = 2.68, 95% CI: 1.21–6.00). Conclusion: CAD is the first cause of SCA in young adults aged less than 40 years. The observed low rates of immediate coronary angiography suggest a missed opportunity for early intervention.